CLINICAL AND INSTRUMENTAL DATA AND SURVIVAL IN DILATED CARDIOMYOPATHY: THREE-YEAR OBSERVATION RESULTS - L. A. Zotova (Klinicist, 2014)
Aim — to assess survival of patients with dilated cardiomyopathy (DCM) in 3‑year follow-up based on clinical history, clinical symptoms, indicators of instrumental methods of examination and tactics of the patients.Materials and methods. 105 patients with diagnosed cardiomyopathy were included in prospective single-center study. Follow‑up period was 3 years or until achieving primary endpoint. Complaints were collected, general clinical research, 6-minute walk test, electrocardiography in 12‑lead were performed annually. Also scale of evaluation of clinical status in patients with chronic heart failure (CHF) in the modification of V.Y. Mareev and assessment of adherence were used annualy.Results. The group of patients with DCM was represented primarily by man, severe heart failure (III–IV functional class) was originally diagnosed in almost 80 % of patients. During the 3 years of follow-up progression of heart failure, worsening of hemodynamic indices were identified in survivors. When evaluating recommended therapy with found that it meets the current guidelines of treatment of heart failure,however, low adherence to treatment of patients was revealed with statistically significant difference between groups of survivors and deceased patients. The annual mortality rate was 20 % and had no significant fluctuations. The main cause of death was heart failure decompensation.Conclusion. Progression of CHF in patients with DCM was confirmed .The most reliable method of assessing the progressive course of heart failure is 6‑minute walk test. The annual high mortality (20 %) indicates an extremely poor prognosis for this disease. The major causes of death were progression of heart failure and sudden cardiac death.